Impact of Workplace Bullying on Psychological Distress: Role of Perceived Organisational Support and Religious Coping - Mei Teh Goi,; Nusrah Samat,; Abdul Mutalib Mohamed Azim, (Asian Academy of Management Journal, 2024)
Despite the fact that perceived organisational support (POS) and religious coping have been advocated as a crucial component of the stress model, the roles remain unclear among academics that often associate with heavy workloads. Therefore, this study aims to examine the moderating role of POS, and the mediating role of religious coping between the relationship of workplace bullying and psychological distress among academics in higher educational institutions (HEIs). Data were collected from academic staff from private and public universities in Malaysia, and a total of 219 data were used. The results revealed that workplace bullying has a positive impact on academics’ psychological distress, and the POS significantly moderated the relationship between workplace bullying and psychological distress. However, this study failed to support the mediating role of religious coping. This study adds to our knowledge of the stress model, by focusing more on perceived organisational support in minimising psychological distress and less on personal resources (religious coping).